Estimation of decoy state parameters for practical QKD - Ali, Sellami; Mahmoud, Omer; Saeed, Rashid Abdelhaleem (INSInet Publications, 2011)
We have presented a method to estimate parameters of the decoy state method based on one decoy state protocol for both BB84 and SARG04. This method has given different lower bound of the fraction of single-photon counts (y1), the fraction of two-photon counts (y2), the upper bound QBER of single-photon pulses (e1), the upper bound QBER of two photon pulses (e2), and the lower bound of key generation rate for both BB84 and SARG04. The numerical simulation has shown that the fiber based QKD and free space QKD systems using the proposed method for BB84 are able to achieve both a higher secret key rate and greater secure distance than that of SARG04. Also, it is shown that bidirectional ground to satellite and inter-satellite communications are possible with our protocol.